Could the Big Technology Companies of Today Be the Financial Advisers of Tomorrow? - Viceira, Luis; Nolan, Peter; Rogers, Terrance; Runco, Anthony (MIT Sloan Management Review, 2018)
Although traditional financial services companies now offer mass-market financial advice via "robo-advisers," average U.S. customers seeking investment advice are still underserved - and platform-based digital powerhouses like Amazon are taking notice.